Hydroxyethyl Starch for Fluid Management in Patients Undergoing Major Abdominal Surgery: A Systematic Review With Meta-analysis and Trial Sequential Analysis. (2nd December 2021) - Pensier, Joris; Deffontis, Lucas; Rollé, Amélie; Aarab, Yassir; Capdevila, Mathieu; Monet, Clément; Carr, Julie; Futier, Emmanuel; Molinari, Nicolas; Jaber, Samir; De Jong, Audrey
Abstract : BACKGROUND: In critically ill patients, warnings about a risk of death and acute kidney injury (AKI) with hydroxyethyl starch (HES) solutions have been raised. However, HES solutions may yet have a role to play in major abdominal surgery. This meta-analysis and trial sequential analysis (TSA) aimed to investigate the effect of HES intravascular volume replacement on the risk of AKI, intraoperative blood transfusion, and postoperative intra-abdominal complications compared to crystalloid intravascular volume replacement. METHODS: In this meta-analysis and TSA, we searched for randomized controlled trials (RCTs) comparing intraoperative HES intravascular volume replacement to crystalloid intravascular volume replacement in adult patients undergoing major abdominal surgery. Primary outcome was 30-day AKI, defined as a binary outcome according to Kidney Disease Improving Global Outcomes (KDIGO) criteria, combining stages 1, 2, and 3 into an AKI category versus no AKI category (stage 0). Secondary outcomes included rates of intraoperative blood transfusion and postoperative intra-abdominal complications. We used random effects models to calculate summary estimates. We used relative risk (RR) as summary measure for dichotomous outcomes, with corresponding 95% confidence intervals (CIs) for the primary outcome ( P value <.05 was considered statistically significant) and 99% CI after Bonferroni correction for the secondary outcomes ( P value <.01 was considered statistically significant). RESULTS: Seven RCTs including 2398 patients were included. HES intravascular volume replacement was not associated with an increased risk of 30-day AKI (RR = 1.22, 95% CI, 0.94–1.59; P = .13), when compared to crystalloid intravascular volume replacement. According to TSA, this analysis was underpowered. HES intravascular volume replacement was associated with higher rates of blood transfusion (RR = 1.57 99% CI, 1.10–2.25; P = .001), and similar rates of postoperative intra-abdominal complications (RR = 0.76 99% CI, 0.57–1.02; P = .02). CONCLUSIONS: In this meta-analysis to focus on HES intravascular volume replacement in major abdominal surgery, HES intravascular volume replacement was not associated with a higher risk of 30-day AKI when compared to crystalloid intravascular volume replacement. However, CI and TSA do not exclude harmful effects of HES intravascular volume replacement on the renal function. Abstract :